Analisis Tentang Salah Satu Gelar Agung Maria Sebagai Ratu Dari Segala Hati: (Analysis of the Mary’s title as Queen of All Hearts) - Batmyanik, Aloysius (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2013)
This article analyzed about the greatest title of Mary based on Anthony M. Buono‘s book which title “The Greatest Marian Title ”. This book contain 24 titles of Mary, but this article focused only on the last title of Mary that is “Mary as Queen of All Hearts”. This article provided several elements related to Mary’s title, as follow: 1) The Culmination, 2) Christ the King of All Hearts, 3) Mary the Queen of All Hearts, 4) Meaning Of the Title, 5) Applications to Us, 6) Prayer to Mary, Queen of All Hearts, and 7) Some Points of Pastoral Implication.